Augmented Reality sebagai Media Pendidikan Interaktif dalam Pandemi Covid-19 - Andis Indrawan, I Wayan; Saputra, Komang Oka; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i01.P07, 2021)
Abstract - In early 2020 various parts of the world announced a pandemic status due to the Covid-19 outbreak caused by the Corona virus. Indonesia is one of the countries affected by this epidemic. The public is urged to implement health procedures such as taking vitamins, basking in the sun, doing physical distancing, staying at home, working from home, Study from Home and so forth. Almost all sectors were paralyzed to minimize the spread of the covid-19 virus. Starting from the tourism sector, the economic sector and even the education sector. The Education Sector, which in its application must run classes in an amount that is not small, must also be limited. Academics and students in various regions in Indonesia are prohibited from traveling on business trips, out of town or even going to schools or educational institutions. One technology that has the potential to be used as an Education medium is Augmented Reality. In the past few years Augmented Reality has launched educational media products for Education in various sectors. In this journal, we will study about augmented reality-based Education media applications that can be used to study at home or Study from Home , so that it can improve physical distancing or reduce mass gathering to help the government in tackling the covid-19 pandemic.